1995
DOI: 10.1051/parasite/1995022163
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive account of species composition, distribution and ecology of phlebotomine sandflies in Jordan

Abstract: Summary:Extensive sampling of 18 localities representing the distinct ecol ogical zones of Jordan was carried out during the sandfly seasons of 1986 to 1988. This resulted in the collection of 21 sandfly species, 8 of which are reported for the first ti me from Jordan. The newly reported species i ncl ude Phlebotomus jacusieli, P. tobbi, P. perfiliewi galilaeus, P. mascitti, P. arabicus, P. halepensis, Sergentomyia palestiniensis and S. taizi. The distribution, relative abundance in domesti c and rural sites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
(13 reference statements)
1
9
0
3
Order By: Relevance
“…vicinity of the lizard-harbouring walls that favour Sergentomyia species), trap type (e.g. light v. sticky), geographical region and seasonality can greatly alter the species composition and sex ratios of collections of Phlebotomus and Sergentomyia (Yuval et al, 1988;Kamhawi et al, 1995;Wheeler et al, 1996;Burkett et al, 2007;Hanafi et al, 2007;Fahmy et al, 2009;Kasap et al, 2009;Kasili et al, 2010). It is important to remember, therefore, that the sex ratios and species compositions reported here only represent trap-related samples and do not necessarily reflect the natural abundances of each gender and species.…”
Section: Discussionmentioning
confidence: 99%
“…vicinity of the lizard-harbouring walls that favour Sergentomyia species), trap type (e.g. light v. sticky), geographical region and seasonality can greatly alter the species composition and sex ratios of collections of Phlebotomus and Sergentomyia (Yuval et al, 1988;Kamhawi et al, 1995;Wheeler et al, 1996;Burkett et al, 2007;Hanafi et al, 2007;Fahmy et al, 2009;Kasap et al, 2009;Kasili et al, 2010). It is important to remember, therefore, that the sex ratios and species compositions reported here only represent trap-related samples and do not necessarily reflect the natural abundances of each gender and species.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the distribution of phlebotomine sandfly species in Jordan [16], Phlebotomus papatasi , the vector of L. major was collected from both domestic and rural areas in many localities in Jordan. It was reported as the predominant or the abundant species in localities where cases were reported in this study such as the Jordan Valley, suburbs of Amman and in the newly reported localities such as Azraq, and Aqaba.…”
Section: Discussionmentioning
confidence: 99%
“…Zoonotic cutaneous leishmaniasis (ZCL) caused by L. major was reported for many years to be the only causative agent prevalent in Jordan mainly in rural areas [16]. In Jordan, the diagnosis of CL cases during the 1960s and 1970s was mainly reported in military hospitals in Amman [11].…”
Section: Introductionmentioning
confidence: 99%
“…A notre avis, chez cette dernière espèce, l'allongement du «bonnet phrygien» est post-traumatique suite à l'intrusion des valves pointues du pénis ce qui explique son inconstance. L'aire de répartition de P. galilaeus est réduite : Chypre, Jordanie (Kamhawi et al, 1995). Palestine (Theodor.…”
Section: Resultatsunclassified